THE ROLES OF ACADEMIC ADVISOR TO THE LEARNING MOTIVATION OF THE SEVENTH SEMESTER STUDENTS’ OF ENGLISH EDUCATION AT ALAUDDIN STATE ISLAMIC UNIVERSITY OF MAKASSAR - Ahmiranil Khairat (Universitas Islam Negeri Alauddin Makassar, 2015)
The objective of this research was to find out the result of the roles of academic advisor to the students learning motivation at the seventh semester students of English Education Department of UINAM. This research was quantitative descriptive by doing survey and conducted at the seventh semester students of English Education Department group 3 and 4 Tarbiyah and Teaching Science Faculty UIN Alauddin in academic year 2014/2015. The total sample of this research consisted of 36 students. This research is conducted by using quantitative approach, the data were collected through questionnaire and descriptive analysis as the data analysis method. The questionnaire was divided into two types, students’ learning motivation questionnaire and the roles of academic advisors. The data analysis and interpretation indicated: (1) There was a medium category from the roles of academic advisors (2) There was a medium category from the students learning motivation. (3) There was a significant relationship between the roles of academic advisors to the students learning motivation. In brief, it could be concluded that there is a significant relationship between the roles of academic advisor to the students learning motivation.